ANALISIS KUALITAS PELAYANAN PUBLIK BADAN PERPUSTAKAAN DAN ARSIP DAERAH PROVINSI RIAU - Yuhelmi Yuhelmi; Nining Sudiar; Rismayeti Rismayeti (Lectura : Jurnal Pendidikan, 2014)
This study aims to analyze How Public Service Board of Library and RegionalArchives Riau Province, hereinafter referred to as (BPAD) Riau Province. This isdone to look at the quality and how much success BPAD Riau Province in performingits main function for the people who need the information in the Library, PublicServices how and what has or has not been done by the libraries in improving servicequality perceptions positively or negatively to quality of public services provided bythe Library Visitors Riau BPAD can be used as input for later followed up todetermine new strategies for improving the quality of services that aim to improve ordefend it.Methods used are qualitative methods and data collected by focuss groupdiscussion (FGD) and inferred based on five aspects of service quality therespondents were library patrons who use library services in BPAD as many as 14people consisting of 2 librarians, lecturers 3, 4 general (civil servants and private), 3students of, and 2 students, by using the technique of purposive sampling. Based FGDresults showed that for BPAD reliability aspects are at a good level, for aspects ofresponsiveness and confidence is at a level sufficient to aspects while empathy is at alevel less so for this aspect needs to be improved towards a better, while for theintangible aspects of BPAD services are at a satisfactory level and this needs to bemaintained in order to remain on the future state of the user satisfactory.